Ten years of research on phase separation absorbents for carbon capture: Achievements and next steps. (September 2016) - Zhuang, Quan; Clements, Bruce; Dai, Junyi; Carrigan, Logan
Highlights: The publications on biphasic or phase separation CO2 absorbents were reviewed. The absorbent systems include non-aqueous, aqueous, conventional amines and lipophilic amines. Other than phase separation, some of the biphasic absorbents have much higher cyclic CO2 loading capacity. This will bring even more extra merit to CCS. Biphasic solvents have potential to reduce energy penalty and the equipment size. More work should be carried out on phase characterization, CO2 absorption and regeneration kinetics, modeling, cost evaluation. Abstract: Since the first disclosure of a patent on biphasic CO2 capture absorbent in 2005, more and more research work has been carried out worldwide looking for new biphasic systems and expanding the earlier achievements. There are two types of biphasic absorbent systems: amine dissolved in alcohol, i.e., non-aqueous system; and less soluble amines (alkanolamines or lipophilic amines, single amine or a mixture of amines) dissolved in water, i.e., aqueous system. Phase separation could happen at absorption temperature or at higher temperature, resulting in a CO2 -rich phase and a CO2 -lean phase. Only the CO2 -rich phase will be regenerated, rendering a smaller regenerator and lower regeneration energy consumption. Some of the biphasic absorbent systems show lower regeneration temperatures and higher regeneration depth compared to aqueous MEA (monoethanolamine), indicating even more potential merits. In this paper, the previous R&D results and data are summarized and reviewed. Future directions for research and development are discussed.